METHOD OF COMPLEX SUBSTANTIATION OF REQUIREMENTS TO THE PARAMETERS OF INFORMATION EQUIPMENT ELECTRONIC COMMUNICATION NETWORKS - SUBACH, IHOR; NEKRUTENKO , VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The relevance of the study is due to the need to ensure the effective functioning of electronic communication networks in the context of limited funding, rapid development of communication technologies and increased requirements for the quality and reliability of electronic communication equipment. The solution to this problem will help to increase the efficiency of planning prospective and modernization of existing electronic communication networks, ensuring their readiness to perform tasks in difficult operating conditions.A method of comprehensive substantiation of requirements for the parameters of equipment of the information direction of electronic communication networks is proposed. It is determined that the problem of complex substantiation of requirements for the parameters of equipment of information directions of electronic communication networks is reduced to the problem of optimal distribution of the allocated resource between the optimization parameters, each of which makes a certain contribution to improving the quality of the network functioning and requires different costs to ensure a given value of the selected quality indicator. It is shown that a comprehensive substantiation of the requirements for the parameters of equipment of electronic communication networks relates to the problem of mathematical programming, in which some variables are continuous, while others can take discrete values. The analysis of the objective functions made it possible to distinguish a set of functional and operational and technical parameters of the equipment of electronic communication networks as variables. To solve the formulated problem, it is advisable to use a procedure based on the idea of direct search - a sequential optimization procedure with the choice of a certain step in the set of values of cost parameters.The developed method makes it possible to scientifically substantiate the quantitative requirements for the functional and operational and technical parameters of the equipment of the information direction of electronic communication networks.
Keywords: equipment parameters; communication networks; functional parameters; operational parameters